METAPHORS OF ORCHID NAMES IN INDONESIAN - I Dewa Putu Wijana (Journey: Journal of English Language and Pedagogy, 2023)
This article aims to reveal several matters concerning metaphorical expressions found in orchid naming practices in Indonesian. By using data collected through google tracing, it is found that many orchid names in Indonesian consist of metaphorical expressions located on the "sub-species" and "characteristics" of the name elements. With regard to the forms, the metaphors can be constructed in the forms of monomorphemic words, polymorphemic words, and phrases. The metaphorical expressions are exploited to resemble with the target domains, i.e., various parts of the plants, mainly the shape and motives of the flower petals, leaf, size of the plant, and root. Various entities are close to human life used as source domains of metaphors, such as animals, human beings, things, plants, sky objects, and others. Most of the source domains are universal, and several of them are culturally specific as reflection of sociocultural realities.